Characterization of inequality changes through microeconometric decompositions : The case of greater Buenos Aires - Gasparini, Leonardo Carlos (2020)
The main economic variables have widely oscillated in the last two decades in Argentina in association with deep macroeconomic and structural transformations. After reaching a peak of 172% monthly in 1989, the inflation rate decreased to less than 1% yearly in a few years; GDP drastically fell at the end of the eighties and then grew at unprecedented rates in the first half of the nineties; unemployment rose steadily from around 5% to 14% in a short period of time. Income inequality was not an exception in this turbulent period. The Gini coefficient increased from 41.9 to 46.7 between 1986 and 1989, fell to 40.0 towards 1991, and rose steadily in the following 7 years, reaching a record level of 47.4 in 1998.1 It is difficult to find in recent economic history periods with such marked changes in inequality, in Argentina as well as in the rest of the world. The reasons of these changes in inequality are varied and complex. The main aim of this paper is to assess the relevance of some forces that are believed to have affected income inequality in the Greater Buenos Aires area between 1986 and 1998. More specifically, the microeconometric decomposition methodology proposed by Bourguignon, Ferreira and Lustig (1998) is used to measure the relevance of various factors that appear to have driven changes in inequality. In particular, this methodology is used to identify to what extent changes in the returns to education and experience, in endowments of unobservable factors (such as individual’s innate ability) and their returns, in the wage gap between men and women, in labor market participation and hours of work, and in the educational structure of the population contribute to explain the observed changes in income distribution.